2013
DOI: 10.1080/10410236.2012.712091
|View full text |Cite
|
Sign up to set email alerts
|

Persuading People with Depression to Seek Help: Respect the Boomerang

Abstract: People with depression are likely to process information with a negative bias when confronted with self-relevant information. Accordingly, we feared exposing depressed people to a public service announcement (PSA) addressing the stigma of depression would possibly boomerang and result in less intention to seek help and in increased self-stigma. College students (N = 271; Mage  = 22.51, SD = 4.71; 63.1% female; 37.3% White, 31.9% Hispanic, 12.9% Asian, 6.8% multiethnic, 3.4% Black, 7.6% other) were randomly ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
30
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
4
3
2

Relationship

2
7

Authors

Journals

citations
Cited by 55 publications
(35 citation statements)
references
References 38 publications
1
30
0
Order By: Relevance
“…This is especially the case when considering that not all of the previous attempts to influence individuals with depressive symptomatology have been successful, and some have even resulted in iatrogenic effects (Keeler & Siegel, 2016;Klimes-Dougan et al, 2009;Lienemann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This is especially the case when considering that not all of the previous attempts to influence individuals with depressive symptomatology have been successful, and some have even resulted in iatrogenic effects (Keeler & Siegel, 2016;Klimes-Dougan et al, 2009;Lienemann et al, 2013).…”
Section: Discussionmentioning
confidence: 99%
“…Highlighting the potential for aversive outcomes, Lienemann, Siegel, and Crano (2013) reported that a message encouraging help-seeking (e.g. "You are not to blame for the cause of your depression.…”
Section: Introductionmentioning
confidence: 99%
“… 9 Meanwhile, previous studies have suggested that depression help-seeking messages have the potential to backfire; exposure to the messages may result in increased self-stigma and increased reluctance to help seeking (ie, boomerang effect). 10 11 Further evidence is needed to identify strategies for successful public health messaging with the aim of promoting access to mental healthcare.…”
Section: Introductionmentioning
confidence: 99%
“…Among those directly targeting help-seeking among people with elevated levels of depressive symptomatology, there have been reports of success (e.g., Syzdek, Green, Lindgren, & Addis, 2016); however, other studies have struggled to achieve the desired impact (e.g., Costin et al, 2009), with some chronicling negative outcomes (e.g., Keeler & Siegel, 2016). For instance, Lienemann, Siegel, and Crano (2013) reported an experimental investigation in which reading a message (i.e., "You are not to blame for the cause of your depression. Depression is treatable if you are willing to seek help.…”
mentioning
confidence: 99%